Should the diagnostic criteria for suspected clinical chorioamnionitis be changed?. (4th March 2021) - Sung, Ji-Hee; Choi, Suk-Joo; Oh, Soo-young; Roh, Cheong-Rae
Abstract: Purpose of review: The criteria for the diagnosis of intra-amniotic infection (IAI) were derived from a study of women at term in labor but is currently used as the main diagnostic tool for clinical chorioamnionitis. Regarding the inconsistent usage of the term, the diagnostic utility of clinical chorioamnionitis needs to be revisited. In this review, we addressed the critical issues on why the diagnostic criteria of suspected clinical chorioamnionitis should be changed. Recent findings: Overall, the accuracy of clinical chorioamnionitis to detect intra-amniotic infection (IAI) is not high, around 50%. The accuracy of each diagnostic criteria to diagnose IAI is, for example, 51.1% with maternal tachycardia, 57.8% with fetal tachycardia, and 55.6% with maternal leukocytosis. However, it needs to be reminded that these diagnostic performances had been obtained from term pregnancies but not from preterm pregnancies. Since there is a difference between clinical chorioamnionitis and histologic chorioamnionitis or even IAI, the diagnostic criteria of clinical chorioamnionitis would be ideal if it could directly predict the development of neonatal infectious outcomes. In fact, multiple definitions of clinical chorioamnionitis either in more lenient or stringent manner are currently used, which is responsible for inconsistent association of clinical chorioamnionitis with long-term neonatal outcomes. Whereas the diagnosis of clinical chorioamnionitis in preterm is followed by expeditious delivery, the diagnosis of clinical chorioamnionitis at term pregnancy is usually conducted in laboring women and requires additional neonatal evaluation for sepsis, which suggests different implications of clinical chorioamnionitis in preterm and term pregnancy. Summary: Current diagnostic criteria of clinical chorioamnionitis should be revised, specifically in terms of sensitivity in preterm pregnancy and specificity in term pregnancy.